PHysical activity Implementation Study In Community-dwelling AduLts (PHISICAL): study protocol. Issue 5 (5th January 2018) - Carpenter, Hannah; Audsley, Sarah; Coupland, Carol; Gladman, John; Kendrick, Denise; Lafond, Natasher; Logan, Philippa; Skelton, Dawn A; Timblin, Clare; Timmons, Stephen; Ward, Derek; Orton, Elizabeth
Abstract : Background: Falls in older people are a leading causes of unintentional injury. Due to an ageing population, injuries are likely to increase unless more is done to reduce older people's falls risk. In clinical trials, the Falls Management Exercise (FaME) programme has reduced the rate of falls and falls-related injuries in community-dwelling older adults. However, the commissioning of FaME is inconsistent across England, potentially due to a lack of evidence that FaME can be delivered effectively in a 'real world' setting. The PHysical activity Implementation Study In Community-dwelling AduLts (PHISICAL) study is designed to study the implementation of FaME in a range of different settings in England. Methods: The PHISICAL study will use a mixed-methods, triangulation, multilevel design to explore the implementation of FaME. Framework analysis of semistructured interviews with up to 90 stakeholders (exercise programme users, service providers, referrers and commissioners) and observational data from locally led communities of practice will identify the factors that influence FaME's implementation. Quantitative, anonymised, routine service data from up to 650 exercise programme users, including measures of falls and physical activity, will allow assessment of whether the benefits of FaME reported in clinical trials translate to the 'real world' setting. Conclusion: The findings from this study will be used to develop a toolkit of resources and guidance to inform the commissioning and delivery of future FaME programmes. This study has the potential to inform public health prevention strategies, and in doing so may reduce the number of falls in the older population while delivering cost savings to health and social care services.